2012
DOI: 10.5334/ijic.850
|View full text |Cite
|
Sign up to set email alerts
|

Case management for at-risk elderly patients in the English integrated care pilots: observational study of staff and patient experience and secondary care utilisation

Abstract: Introduction: In 2009, the English Department of Health appointed 16 integrated care pilots which aimed to provide better integrated care. We report the quantitative results from a multi-method evaluation of six of the demonstration projects which used risk profiling tools to identify older people at risk of emergency hospital admission, combined with intensive case management for people identified as at risk. The interventions focused mainly on delivery system redesign and improved clinical information system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 29 publications
(31 reference statements)
4
95
1
Order By: Relevance
“…the Integrated Care Pilots (RAND Europe, 2012;Roland et al, 2012), the Partnership for Older People Pilots (Windle et al, 2009;Steventon et al, 2011), the Inner North West London Integrated Care Pilot (Nuffield Trust, 2013) -and there is little evidence that these have led to reductions in emergency hospital admissions or cost. (Nolte and McKee, 2008;Goodwin et al, 2013;Mason et al, 2015) Systematic reviews carried out by Cameron et al (2012) have identified factors that help or hinder joint working.…”
Section: "My Care Is Planned With People Who Work Together To Understmentioning
confidence: 99%
“…the Integrated Care Pilots (RAND Europe, 2012;Roland et al, 2012), the Partnership for Older People Pilots (Windle et al, 2009;Steventon et al, 2011), the Inner North West London Integrated Care Pilot (Nuffield Trust, 2013) -and there is little evidence that these have led to reductions in emergency hospital admissions or cost. (Nolte and McKee, 2008;Goodwin et al, 2013;Mason et al, 2015) Systematic reviews carried out by Cameron et al (2012) have identified factors that help or hinder joint working.…”
Section: "My Care Is Planned With People Who Work Together To Understmentioning
confidence: 99%
“…The Partnerships for Older People Projects (POPPs) 2006-09 had an effect on emergency bed days (Windle et al, 2009) and the Integrated Care Pioneers launched in 2013 claim some success in reducing the growth of emergency admissions (NHS England, 2017). However, evaluations of the Evercare pilots of case management for older people 2003-05 (Gravelle et al, 2007) and the Integrated Care Pilots 2009-11 (Roland et al, 2012) failed to show the desired impact on emergency admissions, although other benefits of the programmes were identified. A Nuffield Trust review of community-based interventions concluded that out of more than 30 evaluations, only one intervention had reduced emergency hospital admissions and therefore costs to the NHS (Bardsley et al, 2013).…”
Section: Integrated Care For Older Peoplementioning
confidence: 99%
“…Of the 11 studies, eight were European, consisting of four studies (and five papers) from England, 48,49,52,54,55 two (related studies) in Germany, 27,46 one in Scotland 44 and one in Spain. 53 Three studies were undertaken in North America, one in Canada 45 and two in the USA (yielding three papers).…”
Section: Settingsmentioning
confidence: 99%
“…This included the use of community matrons 48,52,54,55 -senior nurses with a care co-ordination function, 54 who were introduced following Department of Health funding in support of the care of patients with long-term conditions. 60 The intended use of multidisciplinary teams (MDTs) was noted in five studies, 44,45,47,49,54 and virtual wards featured in three. 45,54,56 The virtual ward model is based on the use of predictive models to identify those at risk of emergency admission, and the provision of a period of intensive, multidisciplinary case management at home using the processes and staff associated with hospital wards.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation